(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the linguopoetic nature, types, and main characteristics of wordplay in literary texts from a scholarly perspective. It substantiates that wordplay arises from the creative use of the formal and semantic potential of linguistic units and contributes to the formation of multi-layered meanings within a text. Wordplay based on homonymy, polysemy, paronymy, as well as phonetic, morphological, and syntactic devices is analyzed through illustrative examples. The study also reveals the role of wordplay in enhancing the aesthetic expressiveness of literary discourse, shaping the author’s individual style, and activating the reader’s interpretative thinking. The findings of the research are of both theoretical and practical significance for linguopoetics, stylistics, and literary text analysis.